Anti-Xa versus time-guided anticoagulation strategies in extracorporeal membrane oxygenation: a systematic review and meta-analysis. (July 2021) - Willems, Ariane; Roeleveld, Peter P; Labarinas, Sonia; Cyrus, John W; Muszynski, Jennifer A; Nellis, Marianne E; Karam, Oliver
The purpose was to compare time-based vs anti-Xa-based anticoagulation strategies in patients on ECMO. We conducted a systematic review and meta-analysis using multiple electronic databases and included studies from inception to July 19, 2019. The proportion of bleeding, thrombosis, and mortality were evaluated. Twenty-six studies (2, 086 patients) were included. Bleeding occurred in 34.2% (95%CI 25.1;43.9) of the patients with anti-Xa-based versus 41.6% (95%CI 24.9;59.4) of the patients with time-based anticoagulation strategies. Thrombosis occurred in 32.6% (95%CI 19.1;47.7) of the patients with anti-Xa-based versus 38.4% (95%CI 22.2;56.1) of the patients with time-based anticoagulation strategies. And mortality rate was 35.4% (95%CI 28.9;42.1) of the patients with anti-Xa-based versus 42.9% (95%CI 36.9;48.9) of the patients with time-based anticoagulation strategies. Among the seven studies providing results from both anticoagulation strategies, significantly fewer bleeding events occurred in the anti-Xa-based anticoagulation strategy (adjusted OR 0.49 (95%CI 0.32;0.74), p  < 0.001) and a significantly lower mortality rate (adjusted OR 0.61 (95%CI 0.40;0.95), p  = 0.03). There was no significant difference in thrombotic events (adjusted OR 0.91 (95%CI 0.56;1.49), p  = 0.71). In these seven observational studies, only a small fraction of the patients were adults, and data were insufficient to analyze the effect of the type of ECMO. In this meta-analysis of observational studies of patients on ECMO, an anti-Xa-based anticoagulation strategy, when compared to a time-based strategy, was associated with fewer bleeding events and mortality rate, without an increase in thrombotic events.